The Influence of Digital Political Literacy on Generation Z's Political Participation in Responding to Strategic Issues in Sumedang Regency - Mohammad Nurramdhani; Karim Suryadi; Syaifullah Syaifullah (FKIP - Universitas Riau, 2026)
In Sumedang Regency, high youth electoral participation does not fully reflect critical engagement, as responses remain largely reactive to social media virality. This quantitative study aims to analyze the factual condition of digital political literacy and examine its influence and correlation with the political participation of Generation Z in responding to strategic issues. Using simple linear regression and Spearman Rank correlation analysis, this study surveyed 384 respondents aged 17–29 across 26 sub-districts. Data were gathered through Likert scale questionnaires, observations, and triangulation interviews. Descriptive results show that Generation Z's digital political literacy and political participation are moderate. Hypothesis testing proves that digital political literacy significantly influences political participation (tcount = 23.914 > ttable= 1.966, p = 0.000), with a strong correlation coefficient of 0.774 and a coefficient of determination of 60%. This study concludes that higher substantive digital political literacy is associated with more active and critical youth engagement. Theoretically, it reinforces Participatory Democracy and Civic Online Reasoning theories. Practically, this study recommends the Digital Political Literacy Academy and Regional Issue Analysis Laboratory programs to strengthen critical literacy and political participation of Generation Z.